2016
DOI: 10.3847/0004-637x/826/1/8
|View full text |Cite
|
Sign up to set email alerts
|

Extrasolar Storms: Pressure-Dependent Changes in Light-Curve Phase in Brown Dwarfs From Simultaneous HST and Spitzer Observations

Abstract: We present Spitzer /IRAC Ch1 and Ch2 monitoring of six brown dwarfs during 8 different epochs over the course of 20 months. For four brown dwarfs, we also obtained simulataneous HST /WFC3 G141 Grism spectra during two epochs and derived light curves in five narrow-band filters. Probing different pressure levels in the atmospheres, the multi-wavelength light curves of our six targets all exhibit variations, and the shape of the light curves evolves over the timescale of a rotation period, ranging from 1.4 h to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
175
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(197 citation statements)
references
References 55 publications
20
175
2
Order By: Relevance
“…To date, published light curves of various ultracool dwarfs show single or double peaks, whose shapes vary with time, sometimes even within a single rotation (Artigau et al 2009;Radigan et al 2012;Apai et al 2013;Gillon et al 2013;Buenzli et al 2015;Karalidi et al 2015;Metchev et al 2015;Lew et al 2016;Yang et al 2016). These observations are interpreted as single or multiple cloud structures in the atmosphere of brown dwarfs that can evolve at short timescales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, published light curves of various ultracool dwarfs show single or double peaks, whose shapes vary with time, sometimes even within a single rotation (Artigau et al 2009;Radigan et al 2012;Apai et al 2013;Gillon et al 2013;Buenzli et al 2015;Karalidi et al 2015;Metchev et al 2015;Lew et al 2016;Yang et al 2016). These observations are interpreted as single or multiple cloud structures in the atmosphere of brown dwarfs that can evolve at short timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral contribution functions can be calculated to determine which pressure ranges are probed by which wavelengths. Then, Yang et al (2016) used state-of-the-art radiative transfer models to evaluate changes in the emerging spectrum in response to changing temperatures in discrete pressure levels to determine the contribution functions. This approach is imperfect, as it does not include readjustment of the cloud cover and atmospheric dynamics in response to the temperature change introduced; nevertheless, it can provide a useful guide for the pressure levels probed for different atmospheres at different wavelengths.…”
Section: Spectral Modulations and Cloud Structurementioning
confidence: 99%
“…Synoptic monitoring of objects with patchy clouds is a powerful tool to study such objects because each observation samples different regions of the surface as the target rotates. Spectroscopic monitoring of brown dwarfs with the Hubble Space Telescope (HST) has detected wavelength dependent phase shifts in light curve features (Buenzli et al 2012;Apai et al 2013), best interpreted as due to molecules condensing at different pressure levels within the atmosphere and cloud structures in the vertical as well as horizontal (Buenzli et al 2012;Yang et al 2016), including in some cases the presence of a low pressure haze layer (Yang et al 2015). The chemistry of the clouds varies with the temperature of the brown dwarf photosphere, from the warmest condensates (e.g., various oxides of magnesium and calcium) at T eff ∼ 2500 K to water clouds for the coolest brown dwarfs (Faherty et al 2014;Luhman & Esplin 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Clouds may appear again below 900 K based on the colors of late T dwarfs, this time in the form of sulfides (Morley et al 2012). Photometric variability at near-IR wavelengths has been reported in this temperature regime, which has been attributed to clouds (Yang et al 2016). Among the Y dwarfs (<500 K; Dupuy & Kraus 2013), additional clouds of water and ammonia are predicted to form at <350 K and <200 K, respectively (Burrows et al 2003;Morley et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The spectra of L dwarfs (1300-2200 K; Stephens et al 2009) are best fit by models that include a thick cloud layer of iron, silicates, and corundum (Saumon & Marley 2008). Those clouds break up non-uniformly and disappear as brown dwarfs grow cooler and enter the T dwarf sequence (500-1300 K; Stephens et al 2009), as indicated by the near-infrared (IR) colors (Burgasser et al 2002), photometric and spectral variability (Buenzli et al 2014;Burgasser et al 2014;Radigan et al 2014;Wilson et al 2014;Yang et al 2016), and surface maps Karalidi et al 2016) of objects near the L/T transition. Clouds may appear again below 900 K based on the colors of late T dwarfs, this time in the form of sulfides (Morley et al 2012).…”
Section: Introductionmentioning
confidence: 99%